Financial econometrics : methods and models - Wang, Peijie, 1965- (Routledge advanced texts in economics and finance., 2003)
This book which provides an overview of contemporary topics related to the modelling of financial time series, is set against a backdrop of rapid expansions of interest in both the models themselves and the financial problems to which they are applied.This excellent textbook covers all the major developments in the area in recent years in an informative as well as succinct way.Refreshingly, every chapter has a section of two or more examples and a section of empirical literature, offering the reader the opportunity to practice the kind of research going on in the area. This approach he.